Influence of bentonite in polymer membranes for effective treatment of car wash effluent to protect the ecosystem - Kiran, S. Aditya (Academic Press, 2015)
In this study, modified polyethersulfone (PES) and cellulose acetate (CA) membranes were used in the treatment of car wash effluent using ultrafiltration. Hydrophilic sulfonated poly ether ether ketone (SPEEK) and bentonite as nanoclay were used as additives for the PES and CA membrane modification. Performances of modified membranes were compared with commercial PES membrane with 10kDa molecular weight cut off (MWCO). The influencing parameters like stirrer speed (250-750rpm) and transmembrane pressure (100-600kPa) (TMP) were varied and their effects were studied as a function of flux. In the treatment of car wash effluent, a higher permeate flux of 52.3L/m2h was obtained for modified CA membrane at TMP of 400kPa and stirrer speed of 750rpm. In comparison with modified PES membrane and commercial PES membrane, modified CA membranes showed better performance in terms of flux and flux recovery ratio. The highest COD removal (60%) was obtained for modified CA membrane and a lowest COD removal (47%) was observed for commercial PES membrane. The modified membranes were better at removing COD, turbidity and maintained more stable flux than commercial PES membrane, suggesting they will provide better economic performance in car wash effluent reclamation